Health-related quality of life among people living with HIV in the era of universal test and treat: results from a cross-sectional study in KwaZulu-Natal, South Africa - Reuben Christopher Moyo; Lovemore N. Sigwadhi; Stanley Carries; Zibuyisile Mkhwanazi; Arvin Bhana; Davide Bruno; Eugene L. Davids; Marie-Claire Van Hout; Darshini Govindasamy (HIV Research & Clinical Practice, 2023)
Background The World Health Organisation’s (WHO) key population-based strategy for ending the human immunodeficiency virus (HIV) epidemic is universal HIV test and treat (UTT) along with pre-exposure prophylaxis (PrEP), and post-exposure prophylaxis (PEP). Despite the successful scale-up of the UTT strategy in sub-Saharan Africa (SSA), the quality of life (QoL) of people living with HIV (PLHIV) remains sub-optimal. Poor QoL in PLHIV may threaten the UNAIDS 95-95-95 programme targets. Monitoring QoL of PLHIV has become a key focus of HIV research among other outcomes so as to understand health-related QoL (HRQoL) profiles and identify interventions to improve programme performance. This study aimed to describe HRQoL profiles and identify their predictors in PLHIV in KwaZulu Natal, South Africa. Methods We conducted a secondary data analysis of a cross-sectional survey conducted between May and June 2022 among PLHIV (n = 105) accessing HIV services at an outpatient clinic in KwaZulu-Natal, South Africa. Socio-demographic, HRQoL (EQ-5D-5L index scores), clinical data, depressive symptoms (CES-D-10), and viral load data were collected from all participants. We examined predictors of HRQoL using generalised linear models controlling for age and sex. Results The mean age of the participants was 45 years (SD = 13). The proportion of participants with disabilities and comorbidities were 3% and 18%, respectively. Depressive symptoms were present in 49% of the participants. Participant’s mean EQ-5D-5L index score was 0.87 (SD = 0.21) and ranged from 0.11 to 1.0. The mean general health state (EQ-VAS) was 74.7 (SD = 18.8) and ranged from 6 to 100. Factors that reduced HRQoL were disability (β = −0.607, p ≤ 0.001), comorbidities (β = − 0.23, p ≤ 0.05), presence of depressive symptoms (β = −0.10, p ≤ 0.05), and old age (β = −0.04, p ≤ 0.05). Factors that increased HRQoL were a good perceived health state (β = 0.147, p ≤ 0.001) and availability of social support (β = 0.098, p ≤ 0.05). Conclusion A combination of old age (60 years and above), any disability and comorbidities had a considerable effect on HRQoL among PLHIV. Our findings support the recommendation for an additional fourth UNAIDS target that should focus on ensuring that 95% of PLHIV have the highest possible HRQoL. Psycho-social support interventions are recommended to improve the HRQoL of PLHIV.